TINJAUAN KEINGINTAHUAN SEBAGAI PENDORONG MAHASISWA UNTUK MENGIKUTI PROGRAM MAGANG DAN STUDI INDEPENDEN BERSERTIFIKAT MELALUI VARIABEL SOFTSKILL - Noval Vernando; Rizky Ema Wulansari; Primawati Primawati; Febri Prasetya (Jurnal Vokasi Mekanika (VoMek), 2024)
Higher education in Indonesia plays an important role in developing and enhancing students' knowledge, skills, and understanding across various fields of study, in accordance with the Republic of Indonesia Law Number 12 of 2012 on Higher Education. The "Merdeka Belajar Kampus Merdeka" (MBKM) program has been introduced as part of higher education reform in Indonesia, but there remains a need to understand the factors driving student participation, particularly in the Certified Internship and Independent Study Program (MSIB). This study aims to identify curiosity as a factor driving student participation in the MSIB program through the development of soft skills as a mediating variable. This research employs descriptive analysis with a quantitative approach. Data were collected from 189 students of the Department of Mechanical Engineering FT-UNP through questionnaires and analyzed using SEM with SmartPLS to examine the relationships between curiosity, soft skills, and participation in the MSIB program. The results show that curiosity has a positive influence on student participation in the MSIB program through the development of soft skills. This is indicated by a path coefficient 0.267 and T-statistic value 1.680, suggesting a positive relationship between curiosity and participation in MSIB through soft skills. These findings suggest that to increase student participation in the MSIB program, higher education institutions need to focus on the development of Soft abilities as a crucial component of the educational journey. Moreover, programs that stimulate student curiosity need to be strengthened to prepare them for the workforce with competencies that meet market demands.